Gray’s Personality Dimensions and Reasons for Voluntary Sleep Deprivation Among College Students - Andersz, Nina; Bargiel-Matusiewicz, Kamilla (Frontiers in Psychology, 2018)
Tendency towards healthy and health-risk behavior is associated with external factors, and healthy lifestyle affects its quality. Activation of Behavioral Inhibition System (BIS) and Behavioral Activation System (BAS) and its association with sleeping habits provides insight into the correlates of voluntary sleep deprivation. Aim of the study was to evaluate the relationship between BIS/BAS activity and reasons for voluntary sleep deprivation among young adults and to assess benefits and costs of decreasing sleep duration. Participants were 223 college students. The instruments used were the BIS/BAS Scale, Pittsburgh Sleep Quality Index and a newly developed survey. Statistical analysis was conducted using Mann-Whitney's U-test and Spearman's rho correlation. Increased BIS activity is positively correlated with the frequency of foregoing sleep to study (r=0.19; p<0.01), while activation of BAS Fun Seeking is associated with more frequent voluntary sleep deprivation due to work (r=0.18; p<0.05), social life (r=0.34; p<0.01), and participation in various types of entertainment (p=0.24; p<0.01). Analysis yielded a positive correlation between BAS activity and the amount of perceived benefits of cutting down sleep (p=0.26; p<0.01 for BAS Fun Seeking and p=0.25; p<0.01 for BAS Reward Responsiveness) and the magnitude of BIS activation and the number of perceived losses (r=0.19; p<0.01). Individuals with a higher BAS activity in the Reward Responsiveness subscale more often report choosing sleep deprivation voluntarily (r=0.14; p<0.5). The quality of sleep is related to BIS/BAS activation. The reasons for voluntary sleep deprivation differ depending on the level of BAS/BIS activation.